1, 10-Phenanthroline-dithiine iridium and ruthenium complexes: synthesis, characterization and photocatalytic dihydrogen evolution. Issue 8 (19th June 2018) - Erdmann, E.; Villinger, A.; König, B.; Seidel, W. W.
Abstract : Extending 1, 10-phenanthroline with a dithiine link led to a remarkable increase of the luminescence lifetimes of the respective Ir(ppy)2 and Ru(bpy)2 complexes. Abstract : We report the synthesis and the spectroscopic and electrochemical properties of six mononuclear iridium(iii ) and ruthenium(ii ) complexes bearing S, S ′-extended phenanthroline ligands. Starting from 5, 6-dibromide-1, 10-phenanthroline, the dithiine derivatives N, N ′-1, 10-phenanthrolinedithiino[2, 3- b ]quinoxaline and N, N ′-1, 10-phenanthrolinedithiino[2, 3- b ]benzene were prepared by primary N, N ′-complexation of the dibromo derivative and subsequent nucleophilic substitution at the complex. The photoluminescence of the phenanthroline-dithiine containing complexes shows distinctively increased lifetimes for all Ir(iii ) and Ru(ii ) complexes. The activity of the series of Ir(iii ) and Ru(ii ) complexes as photosensitizers in visible-light photocatalytic water reduction is demonstrated by dihydrogen evolution with a [Fe3 (CO)12 ] catalyst and triethylamine as a sacrificial donor.